Pengaruh model pencegahan stunting berbasis pemberdayaan kader dalam upaya peningkatan pengetahuan dan sikap ibu - Yurissetiowati, Yurissetiowati; Tabelak, Tirza Vivanri Isabela; Yulianti, Hasri; Baso, Namsyah; Wariyaka, Melinda Rosita (JURNAL KESEHATAN PRIMER, 2023)
Background: Stunting is failure to grow and develop in children under 5 years of age and is caused by chronic malnutrition which is characterized by below-normal body length or height. In 2021 in Indonesia, the prevalence of stunting is around 7.9%. Stunting cases in East Nusa Tenggara Province are still high, namely 26.3%, and for the Kupang Regency area, stunting cases have a prevalence of 25.5%. In Oelnasi Village, it was recorded that out of a total of 240 toddlers, 36 toddlers were in the short category and 9 toddlers were in the very short category with a prevalence rate of 18.8%. Objective: This research aims to increase the knowledge and attitudes of mothers of toddlers and prevent stunting in babies by empowering cadres in Oelnasi Village. Method: This type of research is quantitative with a Quasi-Experimental design, pre-test and post-test design. The sample in this study was 60 mothers of toddlers in Oelnasi Village, Kupang Regency. The research instrument used in this study was a questionnaire regarding mothers' knowledge and attitudes towards stunting. Results: Based on the SPSS test on mothers' knowledge and attitudes using the Wilcoxon test, the result was p = 0.001 or a significance level of p < 0.05, which means there is a difference between the mother's level of knowledge and attitudes before and after empowering cadres using the counseling method.